Research progress of the SLFN family in malignant tumors - Yu, Jiale; Guo, Zhijuan; Zhang, Junyi (Frontiers in Oncology, 2024)
The Schlafen (SLFN) gene family has emerged as a critical subject of study in recent years, given its involvement in an array of cellular functions such as proliferation, differentiation, immune responses, viral infection inhibition, and DNA replication. Additionally, SLFN genes are linked to chemosensitivity, playing a pivotal role in treating malignant tumors. Human SLFNs comprise three domains: the N-terminal, middle (M), and C-terminal. The N- and C-terminal domains demonstrate nuclease and helicase/ATPase activities, respectively. Meanwhile, the M-domain likely functions as a linker that connects the enzymatic domains of the N- and C-terminals and may engage in interactions with other proteins. This paper aims to present a comprehensive overview of the SLFN family’s structure and sequence, examine its significance in various tumors, and explore its connection with immune infiltrating cells and immune checkpoints. The objective is to assess the potential of SLFNs as vital targets in cancer therapy and propose novel strategies for combined treatment approaches.